Superhero [compact disc] - Berkner, Laurie (Two Tomatoes Records LLC, 2016)
The Laurie Berkner Band release their first full album of brand new original songs since 2008. The highly anticipated release speaks to kids without talking down to them through imaginative lyrics that enchant and empower.